WCF processing in the L2 curriculum: A look at type of WCF, type of linguistic item, and L2 performance - Leow , Ronald P.; Thinglum , Anne; Leow , Stephanie A. (Studies in Second Language Learning and Teaching, 2022)
Whether type of written corrective feedback (WCF) impacts L2 learning has been investigated for decades. While many product-oriented studies report conflicting findings, the paucity of studies adopting both a process-oriented and curricular approach (e.g., Caras, 2019) underscores the call for further research on: a) the processing dimension of L2 writers’ engagement with WCF in this instructed setting (Manchón & Leow, 2020), b) from an ISLA applied perspective (Leow, 2019a; Leow & Manchón, 2022), and c) any potential relationship with subsequent performances. Also, whether type of linguistic item (e.g., morphological vs. syntactic) plays a role in the processing dimension also warrants further probing. This preliminary quasi-experimental study explored the cognitive processes of 10 adult L2 writers with minimal previous exposure to Spanish interacting with WCF (both direct and metalinguistic) on morphological and syntactic errors. Think aloud data gathered from three compositions written within the natural writing conditions of a foreign language curriculum were transcribed, coded for depth of processing (DoP) (Leow, 2015), and correlated with subsequent performances on the target items. The results revealed: 1) a higher DoP for metalinguistic WCF, 2) differences in processing of linguistic items, 3) similar DoP over time, and 4) a beneficial relationship between DoP and subsequent performances. Recommendations for future research underscore the importance of acknowledging variables within the instructed setting that may impact a pure effect of WCF on L2 development.